2017
DOI: 10.1186/s12944-017-0586-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids: any role in rheumatoid arthritis?

Abstract: BackgroundPolyunsaturated fatty acids (PUFAs) are members of the family of fatty acids and are included in the diet. Particularly, western diet is usually low in n-3 PUFAs and high in n-6 PUFAs. PUFAs play a central role in the homeostasis of immune system: n-6 PUFAs have predominantly pro-inflammatory features, while n-3 PUFAs seem to exert anti-inflammatory and pro-resolving properties. Rheumatoid arthritis (RA) is a chronic inflammatory arthritis in which many inflammatory pathways contribute to joint and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 108 publications
(126 reference statements)
0
63
0
3
Order By: Relevance
“…The setup of these trials was quite heterogeneous in respect to the ω3‐PUFAs preparations, doses, and routes of administration used as well as in respect to the features of the patient cohorts and the clinical parameters used to benchmark therapeutic effects. The results of these trials have recently been exhaustively summarized and analyzed in two systematic reviews . Collectively, most trials investigating the effect in rheumatoid arthritis demonstrated moderate, beneficial effects .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The setup of these trials was quite heterogeneous in respect to the ω3‐PUFAs preparations, doses, and routes of administration used as well as in respect to the features of the patient cohorts and the clinical parameters used to benchmark therapeutic effects. The results of these trials have recently been exhaustively summarized and analyzed in two systematic reviews . Collectively, most trials investigating the effect in rheumatoid arthritis demonstrated moderate, beneficial effects .…”
Section: Introductionmentioning
confidence: 99%
“…The results of these trials have recently been exhaustively summarized and analyzed in two systematic reviews . Collectively, most trials investigating the effect in rheumatoid arthritis demonstrated moderate, beneficial effects . The results on the therapeutic effects of ω3‐PUFAs on psoriasis have been more contradictory with some trials reporting beneficial effects, others finding no effect .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show the importance of PUFAs as essential fatty acids, and their nutritional value in human health and disease prevention. Intake of PUFAs has been associated primarily with decreased risk of cardiovascular diseases and normal brain development [66][67][68]. They also present anti-inflammatory effects and contribute to the good functioning of vision.…”
Section: Nutraceutical Functionsmentioning
confidence: 99%
“…Specifically, the biological activities of essential fatty acids (ALA and LA) influence on the functions and responsiveness of cell membranes, tissue metabolism, hormone signals, and others. The beneficial effects of PUFAs can be mediated by different mechanisms, including altering or regulating cell membrane structures, regulating intracellular signaling pathways, modulating gene transcription, and regulating the production of bioactive lipid mediators or production of eicosanoids (prostaglandins, leukotrienes, and thromboxanes) [68,73].…”
Section: Nutraceutical Functionsmentioning
confidence: 99%